Teach For All: Storytelling "Shared Solutions" and Scaling Global Reform - Chloe Ahmann (Arizona State University, 2015)
Teach For All is a global network of state-based organizations that translate Teach For America's market model of school reform into moral projects of nation-building abroad. Referring to this challenge as one of "scaling" the organization, its leaders elaborate a theory of change that hinges on replicability: in order to effect a global education revolution, Teach For All must reproduce inspiring instances of change in classrooms around the world. In service of this goal, the organization marshals an impressive archive of transformational stories. Each supports its "shared problems, shared solutions" philosophy and attains status as evidence, suggesting that Teach For All's brand of transformative teaching can eradicate educational inequity despite the contingencies of place. Teach For All's use of stories to "sell" this brand of reform is itself nothing new. But what is so peculiar about Teach For All's project is that tales of individual conversion - of situated transformation - come to serve as sites for scalability. By exploring stories as technologies of scale, tracing the ways in which they travel the globe and operate on different audiences, and interrogating the work they do within Teach For All's ideological apparatus, this article explores the relationship between storytelling "shared solutions" and scaling global reform, and the generic subject that such a relationship produces.